2017
DOI: 10.1007/s41101-017-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Seasonal Opportunities to Save Water: Using Weekly Rainfall and Evapotranspiration Patterns to Evaluate Outdoor Water Restriction Policy in South Florida

Abstract: Evaluating trends of historical rainfall and lawn water demand on a weekly and seasonal basis is needed for optimizing lawn and landscape water conservation policy. Outdoor water restrictions are a common conservation strategy and typically feature a Bday of the week^schedule to limit the frequency and duration of urban lawn water use. However, outdoor water restrictions may not necessarily result in more conservative behaviors from end-users. Lawn water demand is directly related to weekly rainfall and evapot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The findings of this paper can apply to both golf course roughs and home lawns because of similar management practices. Furthermore, policymakers may conserve more water during prolonged droughts by restricting irrigation of Meyer to 20–30% ET o rather than imposing traditional restrictions, especially for high irrigators (Boyer et al., 2018; Survis et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this paper can apply to both golf course roughs and home lawns because of similar management practices. Furthermore, policymakers may conserve more water during prolonged droughts by restricting irrigation of Meyer to 20–30% ET o rather than imposing traditional restrictions, especially for high irrigators (Boyer et al., 2018; Survis et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Water restrictions usually limit irrigation to specific hours within a day and/or days within a week (varying from 1–3 d wk −1 ; Boyer, Dukes, Duerr, & Bliznyuk, 2018). With few controls on water application amounts, restrictions can inadvertently promote overwatering (Boyer et al., 2018; Survis, Root, & Pathak, 2017). Furthermore, water restrictions do not factor in differences in water requirements among turfgrass species and cultivars, or dynamics in weather conditions that can dramatically affect the water requirements (Boyer et al., 2018; Survis et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Households had fewer irrigating events per week (mean of 1.3) than allowed under water restrictions (two), but the irrigation applied (mean of 1 in./week) exceeded the target irrigation (mean of 0.3 in./week) in 15 of the 16 weeks, indicating over‐irrigation. In a related study of Palm Beach County, Survis et al () reported that two days/week irrigation at the rates observed in Survis and Root () would have exceeded target irrigation in 99% of the weeks in the study's 20‐year historical period. Households included in the study used either public‐supplied potable water or a private well for irrigation.…”
Section: Introductionmentioning
confidence: 97%